KUALITAS AIR DAN KEANEKARAGAMAN PLANKTON DI DANAU CIKARET, CIBINONG, BOGOR - Soliha, Eha; Rahayu, S.Y. Srie; Triastinurmiatiningsih, - (-)
Lake Cikaret is the largest lake in the village of Cikaret in district of Cibinong, Bogor district which is also a reserve of water for residents. The Lake is thought to have experienced pollution due to the inclusion of various types of waste from households and activities waste disposal by visitors. Research done by the method of field survey, the research is divided into 3 point i.e. inlet, middle and outlet. The results showed the temperature 25 oC-38oC, pH values in the range 5-7, the value of dissolved oxygen content ranged between 5.9-14.5, BOD values ranged from 5.6-7.5 mg/liter and CO2 values ranging between 11.3-13.5 mg/l due to the pollution of the natural. Net primary productivity of photosynthesis 3.2 mg/l, gross 4.3 mg/l of photosynthesis and respiration 1.1 mg/l. Plankton found Chlorophyceae, Cyanophyceae and composed Bacillariophyceae. belong to the phytoplankton and zooplankton 5 classes, namely Euglenoidae, Dapniidae, Maxillo-poda, crustaceans and Monogononta. The value of diversity index includes low range 0.05-0,149. Equity index value on Lake Cikaret range 0,009-0,064. The index value of the dominance on Lake Cikaret range 0.01-0,972. Key words : Lake Cikaret  Cikaret,water quality, plankton